2017
DOI: 10.5296/ajfa.v9i1.11003
|View full text |Cite
|
Sign up to set email alerts
|

The Integration between Strategic Cost Management Techniques to Improve the Performance of Iraqi Manufacturing Companies

Abstract: The performance of manufacturing industry in Iraq has been declining over the last few decades. Worst still, many companies in the manufacturing sector in Iraq are yet to adopt Balanced Scorecard (BSC) to improve their performance despite its potency ensure to achieve competitive advantage and better performance. This study examines the integration between Total Quality Management (TQM) and BSC four perspectives in Iraqi manufacturing industry. Data were collected by means of structured questionnaire survey us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Selling more or saving more are two common ways to increase a firm's profit. e questionnaire outcomes supported that those considerations clearly linked to revenue generation, profit contribution, and quality assurance are more significant to participants for managing costs and further confirmed the definition of strategic costs as those costs directly bringing in revenue, profit, of product value [16,56]. In summary, the results offer evidence that efficiency enhancement and cost reduction without discounting the organisational effectiveness as promoted by Peter Drucker [57], which protects business profit, play an essential role in organisation-wide strategies.…”
Section: No Major Difference For Participants With/withoutmentioning
confidence: 74%
“…Selling more or saving more are two common ways to increase a firm's profit. e questionnaire outcomes supported that those considerations clearly linked to revenue generation, profit contribution, and quality assurance are more significant to participants for managing costs and further confirmed the definition of strategic costs as those costs directly bringing in revenue, profit, of product value [16,56]. In summary, the results offer evidence that efficiency enhancement and cost reduction without discounting the organisational effectiveness as promoted by Peter Drucker [57], which protects business profit, play an essential role in organisation-wide strategies.…”
Section: No Major Difference For Participants With/withoutmentioning
confidence: 74%
“…Previous studies on organizations performance in Iraq were showed indifferent fields of management. Such as, some articles carried out in the area of Knowledge Management [26], Strategic Cost Management [27], economic management and policies [28], public sector organisation's performance in Iraq generally [29] and quality management implementation in oil industry sector [30]. However, except public studies not easy to find an extensive comprehensive study on the performance of Iraqi manufacturing companies.…”
Section: Organizational Performancementioning
confidence: 99%
“…Furthermore, previous reports have shown the low performance of the manufacturing sector in Iraq as well (Bureihi, 2011). This sector is performing poorly due to the low competitive advantage (Al-Naser & Mohamed, 2017). Furthermore, the absence of Iraq in the world competitiveness report showing the low level of competitiveness of Iraq industry.…”
Section: Introductionmentioning
confidence: 99%